Analysis of Students’ Skills in Explaining Tajweed Materials with the UMMI Method - Ikhwandi Ikhwandi; Romelah Romelah; Dina Mardiana (Yayasan Letiges Konsultan Sosial, 2025)
This research aims to answer the problem formulation, namely how skills student to describe Tajweed material with method ummi at TPQ Al Ihsan Archaphada Malang. This study uses a qualitative approach with a case study type to analyze the skills of students in explaining Tajweed material through the Ummi method at TPQ Al Ihsan Archaphadha Malang. Data were collected through observation, interviews with teachers and students, and relevant documentation. Data analysis was carried out with the stages of condensation, presentation, and data verification. The validity of the data was guaranteed through triangulation of sources, techniques and time, namely by comparing the results of observations, interviews, and documentation to ensure the consistency and credibility of the research findings. The results of the study at TPQ Al Ihsan Archaphada Malang, the skills of students in explaining Tajweed material using the Ummi method with the 4 M approach memorizing theory, pointing to models, pointing to books, and evaluating can improve students' understanding of Tajweed material. Students are able to memorize, explain, and apply and explain Tajweed material, such as Nun Sukun/tanwin, Ghunnah, Mim Sukun, Lafadzh Allah, Qalqalah, Hukum Ro', Lam Ta'rif and Mad well. This method makes it easier for students to understand Tajweed systematically, although the laws of Mad, Law of Ro' and Idgham Mutajanisain are still considered difficult by some students. Overall, the Ummi Method has succeeded in improving the ability to read the Qur'an in a tartil and fluent manner.